“Broad” Impact: Perceptions of Sex/Gender-Related Psychology Journals - Brown, Elizabeth R.; Smith, Jessi L.; Rossmann, Doralyn (Frontiers in Psychology, 2022)
Because men are overrepresented within positions of power, men are perceived as the default in academia (androcentrism). Androcentric bias emerges whereby research by men and/or dominated by men is perceived as higher quality and gains more attention. We examined if these androcentric biases materialize within fields that study bias (psychology). How do individuals in close contact with psychology view psychology research outlets (i.e., journals) with titles including the words women, gender, sex, or feminism (sex/gender-related) or contain the words men or masculinity (men-related; Study 1) versus psychology journals that publish other-specialized research, and do these perceptions differ in the general public? While the men-related journal was less meritorious than its other-specialty journal, evidence emerged supporting androcentric bias such that the men-related journal was more favorable than the other sex/gender-related journals (Study 1). Further, undergraduate men taking psychology classes rated sex/gender-related versus other-specialty journals as less favorable, were less likely to recommend subscription (Studies 1–2), and rated the journals as lower quality (Study 2 only). Low endorsement of feminist ideology was associated with less support for sex/gender-related journals versus matched other-specialty journals (Studies 1–2). Decreased subscription recommendations for sex/gender-related journals (and the men-related journal) were mediated by decreased favorability and quality beliefs, especially for men (for the sex/gender-related journals) and those low in feminist ideology (Studies 1–2). However, we found possible androcentric-interest within the public sphere. The public reach of articles (as determined by Altmetrics) published in sex/gender-related was greater than other-specialty journals (Study 3). The consequences of these differential perceptions for students versus the public and the impact on women’s advancement in social science and psychological science are discussed.